The Primo Vascular System as a Possible Exosomal Route Across the Body: Implications for Tumor Proliferation and Metastasis - Chiara Ghiron (Medical Association of Pharmacopuncture Institute, 2019)
This literature study article will present the possibility of a correlation between the energy meridians of Traditional Chinese Medicine, which can be traced back to the recently described primo vessels (formerly known as Bong-Han ducts), their composition, and the ability of tumors to proliferate and metastasize. It is proposed that microvesicular bodies such as exosomes, known to be involved in cell-to-cell communication, immune response, and tumor proliferation, could be moving across the body via the primo vascular system. The ubiquity of the primo vascular system and its penetration through the blood-brain barrier could also explain the ability of some peripheral tumors (e.g., breast tumor) to metastasize in the brain. Keywords: cancer microenvironment, exosomes, hyaluronic acid, primo vascular system, tumor metastasis